Analisa Seting Relai Arus Lebih (Over Current Relai) Pada Transformator Daya 54 MVA di PLTU Tanjung Jati B - Wibiyantoro, Yudhif Prasetyo; , Umar, S.T., M.T (2017)
A global power transformer is indispensable, given the large amount of energy demand used by society. Energy needs are responded by the government by holding a government program that is to create a new plant and unfinished plant to obtain energy 35000 MW. The power transformer is an important component for transmitting that energy. Powerful power transformers can be supported with good protection equipment, one of which is more current relays. More current relays work to detect excess current passing through the system and give commands to the PMT (breaker) for trips or to stop the flow of power to the load which aims to provide protection to the power transformer from the disturbance. Good relay requirements include sensitive, fast, selective, reliable and economical. The method used in the research is the search data required in PT. PLN (Persero) Pembangkitan Tanjung Jati B and search for reference books and scientific journals in accordance with the research. The data obtained is used for mathematical calculations. The sought quantities are nominal current, the ratio of the installed CT, the pickup current, the Instantaneous current, the time delay and the actual current. The value of CT is attached to the primary side 1500: 5 and the secondary side connected to chapter 3500: 5. The results obtained with mathematical calculations, should not exceed the 4.7 A currents on the primary side and 4.45 A on the secondary side. The current value read by the relay exceeds or equal to 4.7 A (primary) and 4.45 A (secondary) then the active relay and PMT will work or trip.